Small Ruminant Lentivirus Infection in Sheep and Goats in North Portugal: Seroprevalence and Risk Factors - João Jacob-Ferreira; Ana Cláudia Coelho; Ana Grau Vila; Delia Lacasta; Hélder Quintas (Pathogens, 2023)
Small ruminant lentiviruses (SRLVs) are transmitted among ovine and caprine species. This disease is a severe problem for small ruminant production, not only for animals’ well-being but also for flocks’ efficiency. The main aim of this research was to quantify the seroprevalence and associated risk factors for SRLV infection in the northern region of Portugal. Samples were collected from a total of 150 flocks, of which 129 (86.0%; 95% CI: 80.67%–91.33%) had at least one seropositive animal. Out of 2607 individual blood samples, 1074 (41.2%) were positive for SRLVs. Risk factors associated with SRLV infection were species (caprine), age (>2 years old), flock size (>100 animals), production system (intensive), food production system (milk), type of activity (professional), participation in livestock competitions (yes), replacement young ewe bought (yes), and natural feeding management (yes). This knowledge empowers the implementation of effective preventive measures. Overall, biosecurity measures should be promoted and implemented with the main aim of reducing viral transmission and reducing the prevalence of this disease. We recognise that government authorities should promote and audit voluntary control and eradication programs in small ruminant flocks in the region studied.